(En)Acting Our Experience: Combat Veterans, Veteranality, and Building Resilience to Extremism - Warner III, Charles Oscar (Journal of Regional Security, 2022)
Drawing from emerging arenas within (applied) anthropology and informed by on-going ethnographic fieldwork alongside combat veterans in Southeast Europe, this paper follows indications that veterans and veteran organizations are potential enablers/maintainers of resilience to violent extremism within societies. This position builds from the recognition that veterans embody a unique capacity for resilience; a capacity generated by surviving combat and deepened as veterans encounter the struggles of life after service. Exploring this proposition of veteran contribution and collaboration suggests a (re)theorization of the veteran in society is required. In service of this (re)theorization, the concepts of “veteranality” and “critical veteranality” are introduced to signify and engage a social ontology representing dynamics of the veteran life-world. In conclusion, it is argued that (re)theorization, ethnographic methodologies and anthropological engagement will guide how socio-political strategies countering extremism can be opened to veteran (en)acted experiences with resilience.
Keywords: veterans; veteranality; resilience; extremism; (applied) anthropology